Holocene glacier and climate variations in Vestfirðir, Iceland, from the modeling of Drangajökull ice cap. (15th June 2018) - Anderson, Leif S.; Flowers, Gwenn E.; Jarosch, Alexander H.; Aðalgeirsdóttir, Guðfinna Th; Geirsdóttir, Áslaug; Miller, Gifford H.; Harning, David J.; Thorsteinsson, Thorsteinn; Magnússon, Eyjólfur; Pálsson, Finnur
Abstract: Drangajökull is a maritime ice cap located in northwest (Vestfirðir) Iceland. Drangajökull's evolution is therefore closely linked to atmospheric and ocean variability. In order to better constrain the Holocene climate and glacier history of Vestfirðir we model the past evolution of Drangajökull ice cap. Simulations from 10 ka to present are forced by general circulation model output, ice-core-based temperature reconstructions, and sea-surface temperature reconstructions. Based on these 10-thousand year simulations, Drangajökull did not persist through the Holocene. We estimate that air temperatures were 2.5–3.0 °C higher during the Holocene Thermal Maximum than the local 1960–1990 average. Simulations support Drangajökull's late Holocene inception between 2 and 1 ka, though intermittent ice likely occupied cirques as early as 2.6 ka. Drangajökull is primarily a Little Ice Age ice cap: it expanded between 1300 and 1750 CE, with the most rapid growth occurring between 1600 and 1750 CE. The maximum Holocene extent of Drangajökull occurred between 1700 and 1925 CE, despite the lowest late Holocene temperatures, occurring between 1650 and 1720 CE. Between 1700 and 1925 CE temperatures were likely 0.6–0.8 °C lower than the 1950–2015 reference temperature. The modern equilibrium line altitude (ELA) is bracketed by topographic thresholds: a 1 °C temperature increase from the modern ELA would eliminate the ice cap's accumulation area, while a reduction of 0.5 °C would lead to the rapid expansion of the ice cap across Vestfirðir. The proximity of Drangajökull to topographic thresholds may explain its late inception and rapid expansion during the Little Ice Age. Highlights: Drangajökull is on the brink of rapid deglaciation. A 1 °C rise in temperature would lead to the complete disappearance of the ice cap. A 0.5 °C decrease in temperature would lead to the rapid expansion of the ice cap. Glacier modeling confirms early Holocene disappearance of Drangajökull. Glacier modeling confirms Drangajökull inception between 2 and 1 ka.